Adenoviral delivery of soluble ovine OX40L or CD70 costimulatory molecules improves adaptive immune responses to a model antigen in sheep - Rojas, José M.; Mancho, Carolina; Louloudes-Lázaro, Andrés; Rodríguez-Martín, Daniel; Avia, Miguel; Moreno, Santiago; Sevilla, Noemí; Martín, Verónica (Frontiers in Cellular and Infection Microbiology, 2022)
The tumour necrosis factor superfamily OX40L and CD70 and their receptors are costimulatory signalling axes critical for adequate T and B cell activation in humans and mice. In this work we inoculated groups of sheep with human recombinant adenovirus type 5 (Ad) expressing Ovis aries (Oa)OX40L or OaCD70 or a control adenoviral vector to determine whether they could improve the immune response to the model antigen OVA. PBMCs and serum samples were obtained for analysis of the adaptive immune response to OVA at days 0, 15, 30 and 90 post-inoculation (pi). Recall responses to OVA were assessed at day 7 and 30 after the second antigen inoculation (pb) at day 90. Administration of these immunomodulatory molecules did not induce unspecific PBMC stimulation. While OaOX40L administration mainly increased TNF-α and IL-4 in PBMC at day 15 pi concomitantly with a slight increase in antibody titer and the number of IFN-γ producing cells, we detected greater effects on adaptive immunity after OaCD70 administration. AdOaCD70 inoculation improved antibody titers to OVA at days 30 and 90 pi, and increased anti-OVA-specific IgG-secreting B cell counts when compared to control. Moreover, higher IFN-γ production was detected on days 7 pi, 7 pb and 30 pb in PBMCs from this group. Phenotypic analysis of T cell activation showed an increase in effector CD8+ T cells (CD8+ CD62L- CD27-) at day 15 pi in AdOaCD70 group, concurrent with a decrease in early activated cells (CD8+ CD62L- CD27+). Moreover, recall anti-OVA CD8+ T cell responses were increased at 7 pb in the AdOaCD70 group. AdOaCD70 administration could therefore promote CD8+ T cell effector differentiation and long-term activity. In this work we characterized the in vivo adjuvant potential on the humoral and cellular immune response of OaOX40L and OaCD70 delivered by non-replicative adenovirus vectors using the model antigen OVA. We present data highlighting the potency of these molecules as veterinary vaccine adjuvant.